Judicial review in Norway : a bicentennial debate / Anine Kierulf. - Kierulf, Anine, 1974- (Comparative constitutional law and policy., 2018)
Outside the United States, Norway's 1814 constitution is the oldest still in force. Constitutional judicial review has been a part of Norwegian court decision-making for most of these 200 years. Since the 1990s, Norway has also exercised review under the European Convention of Human Rights. Judicial review of legislation can be controversial: having unelected judges overruling popularly elected majorities seems undemocratic. Yet Norway remains one of the most democratic countries in the world. How does Norway manage the balance between democracy and judicial oversight? Author Anine Kierulf tells the story of Norwegian constitutionalism from 1814 until today through the lens of judicial review debates and cases. This study adds important insights into the social and political justifications for an active judicial review component in a constitutional democracy. Anine Kierulf argues that the Norwegian model of judicial review provides a useful perspective on the dichotomy of American and European constitutionalism.